Sindrome torácica aguda em pacientes com doença falciforme: caracterização demográfica e identificação de fatores predisponentes - Etienne, Ruth-valine (2023)
Acute chest syndrome (ACS) is the leading cause of morbidity and mortality in patients with sickle cell disease in any age group. Acute chest syndrome is responsible for about 25% of deaths and about 75% of them occur in the age group up to 29 years old, especially in the first decade of life. The etiology of ACS is multifactorial, with both infectious and non-infectious causes being implicated. In infectious causes, we find bacteria, atypical microorganisms, and viruses; noninfectious causes include fat embolism and pulmonary infarction. However, in a large number of cases it is not possible to define the etiology of ACS. Its pathophysiology comprises pneumonia, infarcts, atelectasis, and intrapulmonary falcization. In the lungs, ACS includes complex lung injury and potentially devastating sequelae. Aims: To analyze the prevalence and incidence of ACS in the REDS-III DF cohort and to verify the association between sociodemographic variables, as well as clinical and biological variables, according to the presence or absence of ACS, Methodology: Cross-sectional and descriptive study conducted using data related to Acute Chest Syndrome collected in the multicenter REDS III project. The REDS-III Brazil DF cohort study was designed to assess the pathogenesis of DF and the impact of transfusion on disease outcomes, which is a collaboration between American researchers at the Vitalant Research Institute in San Francisco, California, and researchers at several Hemocenters in Brazil: Hemope, Hemorio, Hemominas, and Instituto da Criança at the Hospital das Clínicas of the Faculty of Medicine of the University of São Paulo. The cohort included patients aged 0-77 years, through interview with project participants, review of participants' medical records and collection of biological material. The project has already been approved by the Research Ethics Committee of the Faculty of Medicine of the University of São Paulo (FMUSP), as well as the Research Ethics Committee of Hemoam. Results: A total of 2793 patients with a diagnosis of sickle cell disease of both sexes took part in this study. 1833 had experienced ACS at least once in their lives, giving a prevalence of 65.6%. The general incidence was 8,3 %, but in children it was 9,5 % . The overall mortality rate was 13.4%, and was higher among adults, 11.2%. The majority of ACS cases occurred in the 11-20 age group (72.4%) and the majority of participants had attended elementary school: 67.9%. The SCD subtypes most associated with the development of STA were HbSS and HbSß0. The history of asthma in STA patients was 88.3% and patients without STA accounted for 11.7%. The majority of patients with ACS had a previous history of VOE: 94.4%. Hemoglobin level was lower and platelet, leukocyte and reticulocyte counts were higher in patients with ACS. Conclusion: The results obtained show the high prevalence of STA in patients with sickle cell disease. These data, especially the mortality rate found, explain why it is considered one of the most frequent and serious complications of the disease